Letter: the diagnostic and prognostic significance of liver histology in alcoholic hepatitis—authors' reply. Issue 6 (23rd August 2021) - Forrest, Ewan; Goldin, Robert
LINKED CONTENT: This article is linked to Forrest et al and Vaz et al papers. To view these articles, visit https://doi.org/10.1111/apt.16157 and https://doi.org/10.1111/apt.16539